2014
DOI: 10.1155/2014/139859
|View full text |Cite
|
Sign up to set email alerts
|

Sedation and Regional Anesthesia for Deep Brain Stimulation in Parkinson’s Disease

Abstract: Objective. To present the conscious sedation and the regional anesthesia technique, consisting of scalp block and superficial cervical plexus block, used in our institution for patients undergoing deep brain stimulation (DBS) for the treatment of Parkinson’s disease (PD).Methods. The study included 26 consecutive patients. A standardized anesthesia protocol was used and clinical data were collected prospectively.Results. Conscious sedation and regional anesthesia were used in all cases. The dexmedetomidine loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Outcomes show promising results, such as good surgical conditions, patient comfort, and analgesia. Furthermore, dexmedetomidine provided a comparable hemodynamic stability during DBS implantation and this trial . A limitation of the present study is that we used an observational design with a small sample size, because our first aim was to examine the applicability of dexmedetomidine.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Outcomes show promising results, such as good surgical conditions, patient comfort, and analgesia. Furthermore, dexmedetomidine provided a comparable hemodynamic stability during DBS implantation and this trial . A limitation of the present study is that we used an observational design with a small sample size, because our first aim was to examine the applicability of dexmedetomidine.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, dexmedetomidine provided a comparable hemodynamic stability during DBS implantation and this trial. 10,11 A limitation of the present study is that we used an observational design with a small sample size, because our first aim was to examine the applicability of dexmedetomidine. Furthermore, we did not add the management of bradycardia in the study protocol because this is part of standard care.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Ozlu et al found that BIS values correlated with the level of sedation in patients with Parkinson's disease undergoing DBS. [19] To our knowledge, there are no studies assessing the use of DOA monitors during GA in patients with movement disorders. Abnormalities in EEG have been reported in patients with Parkinson's disease, and the presence of pathological alpha dominant rhythm was seen in patients with significant cognitive fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…There are only anecdotal observations of variability in the applicability of EEG-derived DOA monitors in patients with neurological disorders and psycho-pharmacotherapy. [18,19] Deep brain stimulation (DBS) is an increasingly popular treatment for patients with movement disorders such as Parkinson's disease and dystonia. Surgery for DBS is usually performed in two stages.…”
Section: Introductionmentioning
confidence: 99%